Hero of the heartland : Billy Sunday and the transformation of American society, 1862-1935 - Martin, Robert F. (Robert Francis), 1946- (Indiana University Press, 2002)
"Robert F. Martin demonstrates nicely that, beneath all of Billy Sunday's flamboyance, the orphan-turned-baseball player-turned-evangelist embodied the tensions of his age. Martin's prodigious research has yielded a wealth of anecdotal material that adds flavor and spice to his keen analysis."--Randall Balmer, author of Mine Eyes Have Seen the Glory: A Journey into the Evangelical Subculture in AmericaWilliam Ashley "Billy" Sunday was the most popular and influential evangelist of his time. Between 1896